2007
DOI: 10.2319/0003-3219(2007)077[0489:badaeo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Bleaching and Desensitizer Application Effects on Shear Bond Strengths of Orthodontic Brackets

Abstract: Because bleaching and desensitizer application significantly affected shear bond strengths of orthodontic brackets on human enamel, they should be delayed until the completion of orthodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 28 publications
4
40
1
1
Order By: Relevance
“…Most authors 2,4,8,12,16 concluded that bleaching adversely affects the SBS of orthodontic brackets when the bonding procedure is performed immediately or delayed by up to 1 month. Bishara et al 6,11 and Uysal et al 5 contradicted the studies that reported adverse effects of bleaching agents on SBS of brackets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most authors 2,4,8,12,16 concluded that bleaching adversely affects the SBS of orthodontic brackets when the bonding procedure is performed immediately or delayed by up to 1 month. Bishara et al 6,11 and Uysal et al 5 contradicted the studies that reported adverse effects of bleaching agents on SBS of brackets.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors 5,6,11 found no adverse effect of bleaching on bond strengths of orthodontic brackets. However, many others 2,7,12 have reported a significant reduction in the bond strength of brackets after bleaching. At-home bleaching is believed to be the most useful and effective bleaching method 13 ; it was first described by Haywood and Heymann 14 in 1989 as nightguard dental bleaching.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, changes in enamel structure and composition induced by these bleaching agents may decrease the shear bond strength (SBS) of orthodontic brackets. 3 Intracoronal bleaching is a conservative alternative to more invasive nonvital esthetic treatments such as crowning or the placement of veneers on discolored teeth. 2 Today, the most commonly used tooth-bleaching agents contain hydrogen peroxide as the active ingredient.…”
Section: Introductionmentioning
confidence: 99%